Natural Logarithm

Definition

The natural logarithm ln:(0,)R is a function defined as follows:

ln(x)=1xdtt.

Properties

Theorem

ln(a)+ln(b)=ln(ab) for a,b>0

Proof
ln(a)+ln(b)=1adtt+1bdtt

Now we use a substitution of u=at in the second integral. In this case we have dudt=a. Furthermore, t=1u=a and t=bu=ab. This change of bounds is the main motivation for this substitution.

ln(a)+ln(b)=1adtt+aabduat=1adtt+aabduu=1adtt+aabdtt=1abdtt=ln(ab)
Theorem

bln(a)=ln(ab) for a>0 and bQ

Proof
bln(a)=b1adtt

We can use a substitution of u=tb which gives dudt=btb1, t=1u=1, and t=au=ab.

bln(a)=b1adtt=b1ab1bdutb=1abduu=ln(ab)

Note that this proof requires that bQ since a general notion of taking an irrational power depends on the exponential function which comes from the natural logarithm. That said, one can prove that it holds in general with that definition.

Theorem

ln(x) diverges as x.

Proof

Consider the area under 1x from 2k to 2k+1 for some kZ+. This area is bounded below by the width of the interval, multiplied by the minimum of the function on the interval, specifically:

2k2n+1dtt12k2k+12k=12.

If we then evaluate this for k=0,1,2 we have that:

ln(2n)=12n1tdt=k=0n12k2k+11tdtk=0n112

Then since k=0n112 diverges as n so does ln(2n).